IDENTITAS SOSIAL ANAK ASUH: STUDI PADA UPTD PSAA HARAPAN BANGSA KALIANDA LAMPUNG SELATAN - Siska Ratnasari; Suhandi Suhandi; Heni Anggraini (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study aims to examine the global issue of increasing child vulnerability caused by poverty, family disintegration, and social instability, which have led to a growing need for alternative care through social service institutions. This condition requires social services that not only fulfill children's physical needs but also foster the development of their social identity as part of their integration into society. The findings indicate that the social identity of foster children is not formed naturally; rather, it is shaped through work programs implemented at the Harapan Bangsa Child Social Care Center (UPTD PSAA), which include social interaction, social guidance, personal development, and gradual social experiences. This study employed a descriptive qualitative approach. Data were collected through field observations, in-depth interviews, and documentation. The data were analyzed deductively using Henri Tajfel's Social Identity Theory, which consists of three dimensions: social categorization, social identification, and social comparison. The results show that the social identity of foster children is not formed naturally but is developed through work programs that serve as agents of social identity formation. These programs include social interaction, social guidance, personal development, and gradual social experiences implemented at the Harapan Bangsa Child Social Care Center (UPTD PSAA).